Beyond the Bitcoin Hype: A Structured Study of Blockchain’s Impact and Potential in Today’s Digital World - Felipe Campos-Rojas; Matheus Franco; Vinicius Minatogawa (Systems, 2023)
The development and application of blockchain-based technologies have been overshadowed by the performance of cryptocurrencies and the belief that these are all that this technology has to offer. This idea has led to the question on numerous occasions if this technology is just expectations or if there are indeed applications that solve problems in today’s world. This bibliometric study on the current state of blockchain applications in the context of digital transformation seeks to break down the myth that this technology is just expectations, synthesizing and ordering the wide variety of topics that arise from this relationship. The results showed that the development of blockchain in the context of digital transformation is growing at an exponential rate, and with this, its applications have come to cover a large part of the industries, interact with other technologies, and establish objectives of all kinds. Based on these topics of technologies, industries, operational objectives, and strategic objectives, a structure is proposed that will serve as a guide for the development of new solutions to some problems, research, applications, and integrations with other technologies.